2010
DOI: 10.1039/b926493k
|View full text |Cite
|
Sign up to set email alerts
|

Combined TPRx, in situ GISAXS and GIXAS studies of model semiconductor-supported platinum catalysts in the hydrogenation of ethene

Abstract: The preparation, characterization and catalytic reactivity of a GaN supported Pt catalyst in the hydrogenation of ethene are presented in this feature article, highlighting the use of in situ characterization of the material properties during sample handling and catalysis by combining temperature programmed reaction with in situ grazing incidence small-angle X-ray scattering and X-ray absorption spectroscopy. The catalysts are found to be sintering resistant at elevated temperatures as well as during reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 61 publications
0
47
0
Order By: Relevance
“…Indeed, in these decades, vigorous research studies have been made on catalytic actions driven by supported metal clusters . It has been shown that catalytic activities of gold clusters supported on the (100) surface of a MgO thin film prepared on a metal surface relate closely to their charge state; a three‐dimensional Au 8 placed an oxygen‐vacancy defect (F centre) of the MgO film reveals a high catalytic activity in the CO oxidation induced by charging due to the electron transfer from the F centre to the Au 8 , while that attached on a defect‐free MgO film has no catalytic activity because of less charging .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in these decades, vigorous research studies have been made on catalytic actions driven by supported metal clusters . It has been shown that catalytic activities of gold clusters supported on the (100) surface of a MgO thin film prepared on a metal surface relate closely to their charge state; a three‐dimensional Au 8 placed an oxygen‐vacancy defect (F centre) of the MgO film reveals a high catalytic activity in the CO oxidation induced by charging due to the electron transfer from the F centre to the Au 8 , while that attached on a defect‐free MgO film has no catalytic activity because of less charging .…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is intuitively straightforward, and its feasibility has been exhibited in hydrogenation reactions. In hydrogenation reactions, H 2 activation can be maneuvered through variations in the electronic structure of metal catalysts supported on semiconductors 12. Nevertheless, the carrier dynamics in the M–S junction are so complicated that the O 2 ‐activation efficacy of this design cannot be warranted.…”
mentioning
confidence: 99%
“…Shape-selective, monodisperse Pt nanoparticles (diameter: 8.1 nm) were prepared according to the polyol process [23,24] and deposited onto the GaN surfaces through spin-coating, thereby resulting in highly reproducible, homogeneous, and stable areal nanoparticle distributions without agglomeration. [11,12] Although this method does not create ordered arrays of nanoparticles, it is suitable for the preparation of low-coverage model catalyst systems to study nanoparticle-support interactions. [14] The total amount of Pt cuboctahedra on the surface was assessed from the nanoparticle diameter (by using TEM) and from the areal density of the nanoparticles (by using AFM).…”
Section: Methodsmentioning
confidence: 99%
“…[9,10] Although its wide bandgap (3.4 eV) severely limits its maximum efficiency under solar illumination, GaN constitutes a model system for the study of semiconductor/electrolyte interfaces and photocatalysis. [11][12][13][14][15] Electrochemical and photocatalytic applications require a fundamental understanding and, eventually, control of interfacial charge-transfer processes, as well as long-term electrode stability. The chemical control of interfacial charge-transfer kinetics is commonly achieved by either the addition of suitable redox agents to the electrolyte or by the deposition of thin metal overlayers onto the electrode.…”
mentioning
confidence: 99%